AN ANALYSIS OF PIDGIN USED BY PEOPLE AT DUSUN KLANTING JATIURIP KREJENGAN PROBOLINGGO - Ela Mustika; Sri Andayani (JURNAL LITERASI, 2022)
The people at Dusun Klanting Jatiurip Krejengan Probolinggo speak Madurese, Javanese, even Madurese and Javanese combination. Their Madurese and Javanese are not in standard. Based on it, this study aims to find out kinds of pidgin and to identify the superstrate of pidgin used by people at Dusun Klanting Jatiurip Krejengan Probolinggo. Pidgin's theory of Holmes (2001) is used in this study to find out the superstrate of pidgin. In describing the data, this study uses descriptive qualitative method as research approach because the data is in description. The result of this study found that pidgin used by people at Dusun Klanting Jatiurip Krejengan Probolinggo are the combination of Madurese and Javanese. From the data, it found 36 words of Madurese and Javanese combination. There are 32 words of Madurese based language and 4 words of Javanese based language. Based on it, Madurese is the superstrate of pidgin used by people at Dusun Klanting Jatiurip Krejengan Probolinggo because Madurese gives more contributions to the form of pidgin.